READING AL-BURHÂN FI USHÛL AL-FIQH BY AL-JUWAINI: A STUDY OF TUBE BABY CASE RESOLUTION - Daruhadi, Gagah (International Journal of Social Service and Research, 2024)
Islamic jurisprudence has been widely used in addressing modern bioethical issues, such as in vitro fertilization (IVF). However, few studies have explored the application of Tafsir Ahkam in modern medical ethics. This research presents a novel approach by integrating classical Islamic judicious principles with modern medical ethical issues. The research is conducted through literature review on classical and contemporary texts related to ushul fiqh and fatwas concerning IVF in Indonesia. The aspects explored include Imam Al-Juwayni's thoughts in his work "Al-Burhan fi Ushul al-Fiqh," the use of the principles of the Islamic law in modern fatwas, and the Islamic legal approach to bioetics. The findings of this study are expected to provide practical recommendations for Islamic scholars and policymakers on how to interpret modern medical issues from an Islamic legal perspective.